Specific features of a closed-end pipe blown by a turbulent jet : aeroacoustics of the panpipes - Meneses Díaz, Felipe Ignacio (2018)
Tesis (Master of Science in Engineering)--Pontificia Universidad Católica de Chile, 2015.